PROSES PRODUKSI PROGRAM ACARA JURNAL9 DI TV9 SURABAYAMENURUT PERSPEKTIF JURNALISTIK ISLAM - Ulki Nazaila; Nur Ainiyah (Fakultas Dakwah Universitas Ibrahimy, 2024)
As the media develops, there are many ways for Muslims to learn and spread the teachings of the Islamic religion. One of them is journalistic media such as print journalism, electronic journalism and online journalism. Journalism itself is an activity of s earching, processing, compiling, editing and presenting an event. The more media develops, the easier it is to access anywhere and by anyone. However, there are some people who abuse the function of the media, such as spreading fake news or hoaxes for cert ain group or personal purposes. Therefore, TV9 Surabaya was moved to create the Jurnal9 program by implementing benefit journalism. TV9 Surabaya is one of the local television stations in East Java which has a religious concept. Because almost all TV9 prog rams contain Islamic elements. Observing the conditions above, researchers are interested in studying the application of Islamic journalism in the Jurnal9 program on TV9 Surabaya. The focus of the problem studied is how the journal9 production process is b ased on an Islamic perspective and what are the benefits of the journal9 program for the people of Surabaya. The aim of this research is to describe the journal9 production process from an Islamic perspective and to determine the benefits of thejournal9 pr ogram for the people of Surabaya. The research method used is qualitative with a case study approach. The data collection techniques use observation, interviews and documentation. The results of this research can be concluded that TV9 has implemented benef it journalism which can be equated with Islamic journalism. The journal9 production process itself uses three stages, namely pre - field, field, and post - field. The Jurnal9 program has the benefits of providing information, educating, persuading and entertai ning, but the benefit of Jurnal9 itself is more dominant in providing information.